Design of Labneh cheese fortified with alginate-encapsulated pepper (Capsicum annuum) extracts - Balabanova, Tatyana; Petkova, Nadezhda; Ivanova, Mihaela; Panayotov, Nikolay (Emirates Journal of Food and Agriculture, 2020)
The aim of the present study was to manufacture fresh cheese Labneh enriched with antioxidative compounds from pepper (Capsicum annuum) extracts encapsulated in alginate beads. The carbohydrate content, total phenolic, and carotenoids content, as well as the antioxidant activity of prepared Labneh samples, were evaluated. The microbiological screening on the 1st and 20th day of storage period at 4 ± 1 °C was performed as well. The obtained results for chemical properties illustrated that the addition of alginate-encapsulated pepper (Capsicum annuum) extracts in Labneh had a significant effect (p<0.05) on the level of total phenols and antioxidant activity in comparison with the control sample. The presence of lactose, galactose and glucose were detected in all samples. It was established that the total viable lactic acid bacterial count (Streptococcus thermophilus and Lactobacillus delbrueckii ssp. bulgaricus) in the experimental samples decreased at the end of the storage period. Coliforms, yeasts, and moulds were not detected in the samples with encapsulated pepper extracts. The sensory evaluation demonstrated a higher score for most Labneh samples with encapsulated pepper extracts in comparison with the control sample. A new cheese product was developed and alginate-encapsulated pepper (Capsicum annuum) extracts were evaluated as a proper approach for the fortification of natural pigments and antioxidants in Labneh samples.